2013
DOI: 10.4322/floram.2013.032
|View full text |Cite
|
Sign up to set email alerts
|

Regime de Regas e Cobertura de Substrato Afetam o Crescimento Inicial de Mudas de Myracrodruon urundeuva

Abstract: O objetivo deste estudo foi avaliar a influência do regime de regas e da cobertura do substrato no crescimento inicial e na qualidade de mudas de Myracrodruon urundeuva. Foram testados três regimes de regas e quatro tipos de cobertura de substrato. As variáveis respostas foram: altura total, diâmetro na base do caule, número de folhas, índice de qualidade de Dickson e sobrevivência. A utilização da lâmina d'água de 12 mm uma vez ao dia, aplicada pela manhã, foi a melhor opção de rega para a produção de mudas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
7
1
9
Order By: Relevance
“…This trend was also observed by Zonta et al (2009), in coffee seedlings, when the increase in irrigation interval reduced the growth in diameter and height. Carvalho et al (2013), in yellow passion fruit seedlings, and Tsukamoto Filho et al (2013), in seedlings of Myracrodruon urundeuva Fr. All of them observed that the growth in stem diameter, height and number of leaves decreased when irrigation frequency changed from daily to alternating, and these results can be associated with the water stress that may occur as the intervals between irrigations increase.…”
Section: Resultsmentioning
confidence: 99%
“…This trend was also observed by Zonta et al (2009), in coffee seedlings, when the increase in irrigation interval reduced the growth in diameter and height. Carvalho et al (2013), in yellow passion fruit seedlings, and Tsukamoto Filho et al (2013), in seedlings of Myracrodruon urundeuva Fr. All of them observed that the growth in stem diameter, height and number of leaves decreased when irrigation frequency changed from daily to alternating, and these results can be associated with the water stress that may occur as the intervals between irrigations increase.…”
Section: Resultsmentioning
confidence: 99%
“…As to the Dickson Quality Index (DQI), none of the treatments evaluated resulted in values equal to the minimum mean (0.20), being the highest DQI referring to the substrate constituted by carnauba residue (0.17). However, it should be emphasized that this minimum mean refers to the Pseudotsuga menziessi and Picea abies species and may not be appropriate to the species in the present study, according to Tsukamoto Filho et al (2013) information in the literature on an adequate DQI related to most forest species is scarce. There was a significant different between the classes of soils for all variables shown in Table 6.…”
Section: Resultsmentioning
confidence: 88%
“…Freitas et al (2017) described the same, considering that various parameters allow nursery manegers to better choose seedlings that will perform better after planting. Tsukamoto-Filho et al (2013) and Lopes et al (2014) also refer to the management practices needed for plantations maintenance and related costs. In addition, a high quality seedling means hight timber production capacity, which is described in Silveira et al (2013) and Faria et al (2013) as the main goal of any forest company in the world.…”
Section: Resultsmentioning
confidence: 99%